Life Satisfaction Among Adolescents: Validation of the Adapted Multidimensional Students’ Life Satisfaction Scale - Anna Tabueva; Victoria Ismatullina; Timofey Adamovich; Artem Malykh; Pavel Kolyasnikov; Sergey Malykh (Behavioral Sciences)
Life satisfaction is associated with adolescents’ adaptability, academic achievement, and mental health, and it reflects the profile of a country’s economic development. In this study, we assessed the psychometric properties of the Russian version of the Multidimensional Students’ Life Satisfaction Scale (MSLSS). The initial adaptation of the MSLSS was performed using a sample of primary school students. Validation on a sample of early-to-middle adolescents is necessary to assess its reliability and validity for this age group. The sample comprised 2826 adolescents between ages 10 and 16 (Mage = 12.6, SD = 1.2, 41.3% girls) who completed the Russian version of the MSLSS assessing their perceived life satisfaction across five scales. While the five-factor structure of the MSLSS was confirmed, the psychometric analysis indicated that the statements function more effectively measured life satisfaction as a singular one-factor construct. We also observed a significant age-related decline in overall life satisfaction and satisfaction with family, self, school, friends, and teachers. Boys reported significantly lower satisfaction with school compared to girls. This study confirms the validity and reliability of the Russian version of the MSLSS, thereby augmenting its general applicability. Furthermore, we replicated previously reported age and gender differences in life satisfaction among early-to-middle adolescents.